2017
DOI: 10.1016/s2468-1253(16)30086-3
|View full text |Cite|
|
Sign up to set email alerts
|

A non-endoscopic device to sample the oesophageal microbiota: a case-control study

Abstract: SummaryBackgroundThe strongest risk factor for oesophageal adenocarcinoma is reflux disease, and the rising incidence of this coincides with the eradication of Helicobacter pylori, both of which might alter the oesophageal microbiota. We aimed to profile the microbiota at different stages of Barrett's carcinogenesis and investigate the Cytosponge as a minimally invasive tool for sampling the oesophageal microbiota.MethodsIn this case-control study, 16S rRNA gene amplicon sequencing was done on 210 oesophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
125
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 41 publications
(47 reference statements)
10
125
0
1
Order By: Relevance
“…in 2009, identified two distinct patterns of EM: type I, associated with normal esophagus and characterized by a predominance of Gram‐positive taxa, with a high abundance of the genus Streptococcus (79%); and type II, associated with erosive esophagitis and BE, and characterized by a predominance of Gram‐negative taxa (mostly from Bacteroidetes, Fusobacteria, and Proteobacteria phyla), with a marked reduction in the Streptococcus abundance (30%). Similar findings were reported in a subsequent study by Liu et al ., whereas recognition of the type I and II patterns was not confirmed by most recent studies employing NGS methodologies, possibly due to differences in patient characteristics (i.e., symptomatic controls, treatment with proton pump inhibitors).…”
Section: The Normal Esophageal Microbiota (Em) and Its Role In Esophasupporting
confidence: 87%
See 4 more Smart Citations
“…in 2009, identified two distinct patterns of EM: type I, associated with normal esophagus and characterized by a predominance of Gram‐positive taxa, with a high abundance of the genus Streptococcus (79%); and type II, associated with erosive esophagitis and BE, and characterized by a predominance of Gram‐negative taxa (mostly from Bacteroidetes, Fusobacteria, and Proteobacteria phyla), with a marked reduction in the Streptococcus abundance (30%). Similar findings were reported in a subsequent study by Liu et al ., whereas recognition of the type I and II patterns was not confirmed by most recent studies employing NGS methodologies, possibly due to differences in patient characteristics (i.e., symptomatic controls, treatment with proton pump inhibitors).…”
Section: The Normal Esophageal Microbiota (Em) and Its Role In Esophasupporting
confidence: 87%
“…Information about healthy EM remains limited, with very few studies enrolling healthy asymptomatic subjects and using culture‐independent techniques. Previous findings were confirmed by recent studies based on next‐generation sequencing (NGS), which demonstrated that the healthy esophagus is dominated by the genus Streptococcus (phylum Firmicutes), in association with Prevotella (phylum Bacteroidetes) and Veillonella (phylum Firmicutes), although at less abundance. Other frequently identified genera included Fusobacterium (phylum Fusobacteria), Haemophilus , Neisseria (phylum Proteobacteria), and Porphyromonas (phylum Bacteroidetes) (Table ), reinforcing the notion that the esophageal microenvironment is phylogenetically closely related to that found in the oropharynx …”
Section: The Normal Esophageal Microbiota (Em) and Its Role In Esophamentioning
confidence: 59%
See 3 more Smart Citations